Review on Pharmocological Properties of Aaka (Calotropis procera) - Paul, Amandeep; Kumar, Antul (International Journal of Economic Plants, 2018)
Calotropis procera belongs to the family Asclepiadaceae. It is commonly known as Madar and well known for its medicinal value. Its medicinal properties are explain in Unani medicinal system and regarded as a useful tribal shrub. India has a huge diversity of rural and tribal community still depends upon medicinal plants. The genuscontained a large group of chemical compounds that exert many pharmacological effects. The plant parts have significant therapeutic value even in fresh or in dry form and exhibits valuable activity against diarroheal, malaria, diabetes, inflammation, helmintic, sterility, spasmodic, hepatic, carcinogenic and skin diseases. The present article is an attempt to provide collective information on phytochemical and pharmacological of shrub.